Transmission Congestion Management using a Wind Integrated Compressed Air Energy Storage System - Gope, S.; Goswami, A. K.; Tiwari, P. K. (Engineering, Technology & Applied Science Research, 2017)
Transmission congestion is a vital problem in the power system security and reliability sector. To ensure the stable operation of the system, a congestion free power network is desirable. In this paper, a new Congestion Management (CM) technique, the Wind integrated Compressed Air Energy Storage (WCAES) system is used to alleviate transmission congestion and to minimize congestion mitigation cost. The CM problem has been solved by using the Generator Sensitivity Factor (GSF) and the Bus Sensitivity Factor (BSF). BSF is used for finding the optimal location of WCAES in the system. GSF with a Moth Flame Optimization (MFO) algorithm is used for rescheduling the generators to alleviate congestion and to minimize congestion cost by improving security margin. The impact of the WCAES system is tested with a 39 bus system. To validate this approach, the same problem has been solved with a Particle Swarm Optimization (PSO) algorithm and the obtained results are compared with the ones from the MFO algorithm.